Analisis struktur pasar rumput laut di Kabupaten Buton Selatan - Kardianto, La Ode; Sarinah; Riani, Irdam; Siang, Roslindah Daeng; Sidiq, Azwar (Jurnal Sosial Ekonomi Perikanan, 2023)
This study aimed to determine the market structure of seaweed in Buton Selatan Regency.   The sampling technique in this study used the Slovin formula with a standard error of 10%. Analysis methods of market structure of seaweed including market share, barriers to entry and exit of the market and knowledge of seaweed market. The analysis results showed that the existing marketing structure of seaweed in South Buton Regency was a market share of difference 44%, the barrier to entry into seawed marketing was quite large because the MES value was above 10%. The determination of price of seaweed was determined by city collectors who have adjusted the selling price of seaweed in Makassar. Therefore, price determination of practice that occurs in the marketing of seaweed tends to the oligopsony market.